Uji Kemampuan Anti Nyamuk Elektrik Serbuk Alang-Alang (Imperata Cylindrica) Terhadap Kematian Nyamuk - Sartika Fathir Rahman; Yunicho Yunicho; Sarimita A. Sangaji (Lontara Journal of Health Science and Technology, 2023)
Mosquitoes are small and slender insects. The body consists of three separate parts, namely the head (caput), chest (thorax), and abdomen. Every year, hundreds of millions of cases of disease transmission to humans occur through insects. This poses a global public health challenge because it spreads widely and rapidly. It is known as arthropod-borne disease or "vector-borne disease. The purpose of this study was to determine the anti-mosquito ability of Satintail Powder (Imperata cylindrica) against mosquito death. The type of research is quasi-experimental research. The results of this study indicate that the mortality of mosquitoes at a concentration of 600 mg is 3 mosquitoes with a time of 2 hours at 30°C, a concentration of 800 mg is 7 mosquitoes with a time of 1 hour at a temperature of 30 °C, and a concentration of 1000 mg is 10 mosquitoes with a time of 45 minutes at 30°C. So, it can be stated that there is a difference in the number of mosquito deaths between the concentrations compared.